Development of environmental literacy and environmental identity of students – how “green” are the curricula in Serbia, Slovenia, and Finland? - Zorica P. Veinović; Sanja R. Blagdanić; Мilica V. Маrušić Jablanović (Inovacije u Nastavi, 2025)
Developing environmental literacy and environmental identity are important goals of education in the modern world faced with numerous environmental challenges. The environmental orientation of a country’s education system is evidenced by its curricula as important indicators of knowledge, proenvironmental attitudes, values, and behaviours that society wants to develop in young generations. The aim of the research was to examine, using a comparative analysis of the curricula for the younger primary school age in Serbia, Slovenia, and Finland, to what extent they include incentives for the development of environmental literacy and environmental identity and whether these incentives are consistent and continuous. The analysed corpus consisted of the curricula for the compulsory subjects in which natural science content is studied in the mentioned countries. The analysis of the curricula was organised in relation to five categories created on the basis of the characteristics and components of environmental literacy and environmental identity. The highest representation of the category Knowledge and Understanding of Environmental Content is common to all three countries. Moral reasoning and students’ affective attitude towards nature are more developed in Slovenian and Finnish curricula than in Serbia. A similar situation was identified relative to the training of students to research environmental issues and interpret the collected data. Incentives for the development of this ability appear more consistently andcontinuously in Slovenia and Finland, with a slightly higher presence in Finland, especially when it comes to critical thinking about environmental issues. Incentives for students’ pro-environmental behaviour are not represented to the same extent in the analysed curricula, and differences were detected in terms of the indicators on which the focus is and the level of generality of the formulations that cover them. The obtained results indicate that there is room for progress in all these curricula in terms of encouraging the development of environmental literacy and ecological identity. In the context of Serbia, it would be desirable to create these incentives more thoughtfully and clearly, primarily through learning outcomes and educational standards, which would consequently influence not only teaching, but also textbooks and initial teacher education.